Searching guidelines for scalable and controllable design of multifunctional materials and hybrid interfaces: Status and perspective - Echeverrigaray, Fernando G.; Alvarez, Fernando (Frontiers in Chemical Engineering, 2022)
The urgent need to address the global sustainability issues that modern society is currently facing requires the development of micro- and nanotechnologies, which rely largely on functional materials. Beyond studies focused solely on low-dimensional materials, broader research related to multifunctionality has shown that the major efforts to meet these criteria of new electronic, photonic, and optoelectronic concepts, particularly to achieve high-performance devices, are still challenging. By exploiting their unique properties, a comprehensive understanding of the implications of research for the synthesis and discovery of novel materials. The present article encompasses innovation research as an alternative optimization and design for sustainable energy development, bridging the scaling gap in atomically controlled growth in terms of surface heterogeneity and interfacial engineering. In addition, the corresponding research topics are widely regarded as a scientometric analysis and visualization for the evaluation of scientific contributions into the early twenty years of the 21st century. In this perspective, a brief overview of the global trends and current challenges towards high-throughput fabrication followed by a scenario-based future for hybrid integration and emerging structural standards of scalable control design and growth profiles are emphasized. Finally, these opportunities are unprecedented to overcome current limitations, creating numerous combinations and triggering new functionalities and unparalleled properties for disruptive innovations of frontier technologies.